Figure skating and sports biomechanics: The basic physics of jumping and rotating - Arnold, A. S.; King, D. L.; Smith, S. L.
Rotation is governed by the principle that angular momentum (determined by both body position and rotation speed) does not change once the skater leaves the ice. Therefore, the skater must generate as much angular momentum as possible during take-off for a multi-revolution jump. Once in the air, a skater controls speed of rotation by closing or opening the body position. To achieve the tightest position as quickly as possible, the skaters in this study lifted their arms less and brought the knee of the free leg up less high in the triple Axel than in the single or double Axel. Jump height and flight time were similar for the single, double and triple Axels. However, horizontal distance covered was much less for the triple Axel, possibly related to the greater skid length and width noted on the triple Axel take-offs, and possibly related to the slower approach speeds observed by coaches (but not yet measured). An understanding of these principles should help in teaching and learning multi-revolution jumps.